(untitled) (World Bulletin of Public Health, 2023)
Ischemic heart disease still remains the dominant pathology among diseases of the cardiovascular system. Surgical revascularization of the myocardium is known to be the most radical way of treating patients with ischemic heart disease [3,4,7]. Due to the progression of percutaneous interventions, the contingent of cardiac surgery patients has changed markedly. To date, the number of patients with the so-called compromised distal bed has increased. Among the candidates for open myocardial revascularization, the percentage of complicated forms of coronary artery disease has increased: acute coronary syndrome, postinfarction cardiosclerosis, dysfunction of the valvular apparatus of the heart of ischemic genesis, decompensated heart failure. The expansion of indications for PCI led to an increase in the percentage of complicated forms of coronary heart disease in the structure of morbidity among candidates for surgery: pronounced decompensation of CHF, dysfunction of the valvular apparatus of ischemic genesis, acute coronary syndrome, extensive cicatricial changes of the myocardium.Patients with severe concomitant pathology increase accordingly: generalized atherosclerosis of the aorta and its branches, cerebrovascular disease, diabetes mellitus, malignant course of arterial hypertension (AH) with damage to target organs, respiratory failure, renal failure